KONSEP TATA RUANG DI ATAS PERAIRAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 85/PUU-XI/2013 - Wiguna, Nicholas Patrick; Warka, Made (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
According to the Constitutional Court, the Water Resources Law cannot implement and re-enact Law Number 11 of 1974 on Irrigation, which transforms the administration of water resources, including waterways, from privatization. After the Constitutional Court's 85/PUU-XI/2013 judgment, this research examined spatial planning above seas. This study and the Constitutional Court's Decision Number 85/PUU-XI/2013 confirmed that waters are state-controlled common property to be used for the people's benefit in accordance with Article 33 paragraph (2) and paragraph (3) of the 1945 Constitution. Changes in license terminology from "Coastal Waters Operating Rights" to "Suitability of Marine Space Utilization Activities". Coastal users must have central government marine space utilization utilities. Permits for maritime space utilization must be evaluated using the 6 air resource management principles.